The Minor Prophets as Christian scripture in the commentaries of Theodore of Mopsuestia and Cyril of Alexandria - Ondrey, Hauna T. (Oxford Early Christian Studies, 2018)
This work compares the Minor Prophets commentaries of Theodore of Mopsuestia and Cyril of Alexandria, isolating the role each interpreter assigns the Twelve Prophets in their ministry to Old Testament Israel and the texts of the Twelve as Christian scripture.